Benefiting 5000 fish farmers in Myanmar: Digital climate advisories with microfinance - Swaans, Cornelis; Khaung, Ye (2024)
From July 2023 to January 2024, 5,000 fish farmers from 20 townships in four regions, including Irrawaddy Delta, used aqua-climatic advisories in their planning and decision-making to reduce climate risks and obtain support to access credit. Within the context of the project DeRISK SE Asia and the CGIAR research initiative Asian Mega-Deltas, Village Link Company Ltd with support of the Alliance of Bioversity International and CIAT provided climate advisory services and provision of loans to selected fish farmers by Microfinance Institutions (MFIs). Aqua-climatic advisories were developed based on the monthly and weekly weather forecasts and Decision Trees for different climate scenarios.